Evolución de la pedagogía tradicional a la escuela de hoy - Lizarazo Rodríguez, Heidy Carolina; Barco Cárdenas, Esperanza (Reflexiones metodológicas y epistemológicas en torno a las prácticas pedagógicas contemporaneas, 2021)
The current societies increasingly value the knowledge of holistic way and specifically in the field of education - teaching. New paradigms that allows you to view the facts or changing phenomena of a new optical drive, the dialectic and the dynamics of the pedagogy - teaching - education is evidence that we are in the presence of a globalized world where it is essential to generate new technologies that meet the needs of society. Any effort you make the human being to obtain knowledge must be privileged. The action to investigate must be seen as a collective act whose product contributes to the scientific and technological development. The overall aim of the research is to: Raise constructive criticism of the current teaching in their pedagogical praxis and its new forms of teaching that characterize it and distinguish it from its didactic classifying it between a traditional or innovative teaching.